A review of the relationship between student growth mindset and self-regulated learning - Kate M. Xu; Jesper Leferink; Lisette Wijnia (Frontiers in Education)
Self-regulation is a crucial life skill. In particular, self-regulated learning (SRL) is an important factor in achieving academic success. Recent research has studied the association between SRL and growth mindset, a belief that emphasizes the importance of effort, perseverance, and the use of SRL strategies. Although recent research indicates positive associations, some findings are contradictory. This review systematically synthesized recent literature on the relationship between students’ growth mindset and SRL in educational settings (e.g., school, college and university students), based on 10 peer-reviewed empirical studies with 15 samples published in English between 2010 and 2023. The studies were coded using a coding scheme. All studies examined a direct relationship between a growth mindset and SRL. The results showed that having a growth mindset is positively associated with SRL strategies overall (r = 0.40). The systematic review then revealed that there are positive associations across all phases of SRL, although with substantial variation in the strengths of the association across studies (also supported by Q statistic, p < 0.001). The results further suggest that the operationalization of mindset measures and socioeconomic disadvantage may moderate the association between mindset and SRL; however, more research is needed on the moderating and mediating factors that affect the relationship between growth mindset and SRL strategy use. These findings suggest that promoting a growth mindset could be a promising factor in interventions designed to foster SRL. Future research could further explore this area of research by taking into account how different contexts and conditions influence this relationship, for example, whether this relationship vary for growth mindset in different school subjects.